Use value of indigenous range grass species in pastoral northern Kenya - Omollo, Erick Ouma; Wasonga, Oliver Vivian; Chimoita, Evans L. (Ethnobotany Research and Applications, 2023)
Background: Land degradation is a major challenge facing the world today, with devastating effects particularly among communities inhabiting semi-arid rangelands who are more directly dependent on natural resources. Over the years, indigenous grasses have provided multiple economic, ecosystem and cultural benefits for many communities in Kenya. However, they have increasingly experienced declining abundance, diversity and productivity over the years, compromising their benefits. This study was conducted to assess use value and local knowledge of indigenous grasses among pastoral communities in Isiolo and Samburu Counties in northern Kenya. Methods: Ethnobotanical data were computed and ranked based on four use indices: relative frequency of citation, relative importance index, cultural value index and cultural importance index. Four key use-categories of the grasses were identified including livestock forage, erosion control, thatching and making hay for sale. Results: Top ranked grasses across these use-categories included Pennisetum mezianum, Chrysopogon plumulosus, Heteropogon contortus and Sporobolus helvolus. These are perennial grasses with multiple uses and are available in wet and dry sessions and in drought periods. While trend analysis revealed overall declining availability of indigenous grasses over recent decades, it strongly came out that the four above-mentioned most preferred species had highest declining availability as perceived by local communities. Conclusions: These findings indicate need for enhanced actions for conserving indigenous grasses considering their multiple benefits and declining availability. Practical local knowledge, traditional structures and their pasture management models are great opportunities for creating responsive actions for rehabilitating degraded critical grazing areas while conserving key indigenous grasses. Keywords: Biodiversity loss, community knowledge, drylands, ethnobotanical, indigenous grasses, Kenya